Dampak Evaluasi Pendidikan terhadap Kualitas Lulusan MI Gagaksipat 2 - Ridha, Ahmad Rasyid; Winarno, Dwi; Tisnawati, Tin; Soleha, Zachro; Kurniawati, Wakhidah (Lembaga Yasin AlSys, 2025)
This study aims to analyze the implementation of educational evaluation at MI Gagaksipat 2 by focusing on the methods, techniques, and challenges encountered. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings reveal that formative evaluation is conducted periodically through quizzes, discussions, and assignments to provide immediate feedback, while summative evaluation is carried out at the end of the semester to measure students' overall achievements. Academically, the evaluation effectively improves student performance, as evidenced by annual increases in academic scores. From a character development perspective, the evaluation shapes students with strong religious values, discipline, and good social skills. Challenges include teachers' limited understanding of complex evaluation techniques and inadequate technological resources. The study recommends providing evaluation training for teachers and adequate facilities to enhance the quality of Islamic values-based learning.